European Concerted Action on Anticoagulation (ECAA) - The Multicentre Calibration of Rabbit and Human ECAA Reference Thromboplastins - Poller, L; Barrowcliffe, T W; van den Besselaar, A M H P; Jespersen, J; Tripodi, A; Houghton, D; Prepared on behalf of the ECAA by the above steering committee (Thrombosis and Haemostasis, 1996)
Two candidate ECAA reference preparations have been calibrated in a multicentre exercise at 14 representative national laboratories to provide reference thromboplastin for a large field study in 16 European countries. Two preparations were required because of the established differences in ISI arising from the two main routes of calibration via rabbit and human IRP. To be comparable with working reagents in everyday use a human plain recombinant reagent of low ISI and a rabbit plain preparation of moderately high ISI were selected. A precise calibration of the two candidate preparations has been achieved with the manual PT technique and an ISI of 0.95 (SE 0.0078) for the human reagent and 1.67 (SE 0.0322) for the rabbit reagent.